GIS-based multi-criteria land suitability assessment for potential agroforestry area expansion in Uttarakhand - Mishra, Deepak Kumar; Kumar, Ujjwal; Arunachalam, Kusum (Indian Journal of Agroforestry, 2023)
In the western Indian Himalayan region, deforestation or forest degradation due to human activities, soil erosion due to intensive farming, and fallow land due to migration, it becomes necessary to make conservation efforts. The present study aims to assess the suitability of the land that has the potential to be used for agroforestry expansion. Land use mapping was done using supervised image classification on Landsat 8 OLI satellite data. The result showed that the agroforestry area was abundant at the altitude